Follow-up of human adenovirus viral load in pediatric hematopoietic stem cell transplant recipients - (:unkn) unknown (WILEY, 2021)
Background: The spectrum of human adenovirus (HAdV)-related disease is broad, and the virus acts on many organs and systems in hematopoietic stem cell transplantation (HSCT) recipients. We aimed to evaluate the effect of HAdV-DNA positivity with clinical and laboratory findings 4 months after HSCT. Methods and results: We retrospectively investigated HAdV-DNA in 153 HSCT recipients (<= 18 years) by quantitative real-time polymerase chain reaction (RealStar; Altona Diagnostics). The results of samples from January 2014 to December 2017 are included. HAdV-DNA was positive for at least one sample type in 50 (32.67%) patients. HAdV-DNA positivity rate was 8.92% (N: 145/1625), 40.25% (N: 64/159), and 25% (N: 2/8) for plasma, stool, and urine samples, respectively. HAdV-DNA was positive in the plasma of 38 (24.83%) patients at a median 16 (range: 1-58 days) days after HSCT. The mortality rate was 23.68% and 6.95% in plasma HAdV-positive and HAdV-negative patients (p = .014). Moreover, HAdV-DNA positivity had an impact on overall survival for allogeneic-HSCT (p = .013), with the cumulative effect including graft-versus-host disease state in multivariate analysis (p = .014). Conclusions: Plasma HAdV-DNA positivity is a potential influencer that decreases survival in the early post-transplant period. Due to the high mortality rates, close monitoring is required of HAdV infections after HSCT with sensitive methods, especially at the early stage.
Keywords: hematopoietic stem cell transplantation; human adenovirus; quantitative polymerase chain reaction; survival